2014
DOI: 10.3329/sja.v11i1.18373
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of ready-to-eat fish ball in curry

Abstract: Fish ball in curry (FBC) was prepared following standard recipe. Prepared FBC was packed in standup pouches and stored at 0 to -2°C. The organoleptic scores for overall acceptability of the FBC were slightly decreased within the storage period (12 days). The pH decreased from 6.38 to 6.07, while peroxide value increased from 2.27 to 9.47. The total volatile base-nitrogen (TVB-N) increased from 5.04 to 17.64. The total plate count increased from an initial value of 1.8 x 10 2 to 2.4 x 10 4 cfu g -1 during chill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…In their study the found a significant (p<0.01) reduction of pH from 4.63 to 4.00 of pickle prepared with small freshwater prawn Macrobrachium dayanam. Kolekar and Pagarkar (2013) observed that-the pH decreased from 6.38 to 6.07 of prepared fish ball curry within the storage period of 12 days which was more or similar to the present finding. In the present study pH of fish condiment stored at refrigeration and frozen temperature decreased slowly.…”
Section: The Ph Valuesupporting
confidence: 91%
“…In their study the found a significant (p<0.01) reduction of pH from 4.63 to 4.00 of pickle prepared with small freshwater prawn Macrobrachium dayanam. Kolekar and Pagarkar (2013) observed that-the pH decreased from 6.38 to 6.07 of prepared fish ball curry within the storage period of 12 days which was more or similar to the present finding. In the present study pH of fish condiment stored at refrigeration and frozen temperature decreased slowly.…”
Section: The Ph Valuesupporting
confidence: 91%
“…TVB-N value was found to be 3.5 mg/100g in horse mackerel surimi at 150 days of frozen storage by K€ ose and Uzuncan (1999), which also supported the results of the present study. The increased trends in TVB-N values with the increased chilled and frozen storage time were also reported for many value-added fishery products (Khanipour et al, 2014;Kolekar and Pagarkar, 2013). The present study (Table 4) also showed similar trends where the TVB-N values were increased in both the hilsa products with the progress of storage time, but the values remained within the acceptable limit.…”
Section: Tvb-nsupporting
confidence: 88%
“…The TPC's results can be useful to judge the shelf-life or forthcoming changes of sensory in a food product [33]. The initial total plate count (TPC) of crab balls in this study was 3.0 log CFU g -1, and the low initial TPC in balls indicated very good quality; this is lower than the initial TPC (4 log CFU g -1 ) of the fish ball [34] and relatively higher than the initial TPC of the fish ball in curry [35]. The maximum microbiological limit for frozen products is 7 log CFU g -1 [37].…”
Section: Discussionmentioning
confidence: 72%